Multidrug Resistance of Escherichia coli Strains Isolated From Bovine Feces and Carcasses in Northeast Mexico - Martínez-Vázquez, Ana V.; Vázquez-Villanueva, Jose; Leyva-Zapata, Luis M.; Barrios-García, Hugo; Rivera, Gildardo; Bocanegra-García, Virgilio (Frontiers in Veterinary Science, 2021)
In this work, the antimicrobial resistance profile of Escherichia coli strains (n = 248) isolated from bovine feces and carcass samples from Tamaulipas, Mexico, was evaluated. Susceptibility to 12 antibiotics conventionally used in human and veterinary treatments was determined according to Clinical and Laboratory Standards Institute guidelines. Genes encoding resistance to tetracycline (tetA and tetB), streptomycin (strA), aminoglycoside (aadA), and β-lactamase (blaTEM and blaSHV) were investigated by PCR. Also, stx1, stx2, eae, bfp, and hlyA encoding virulence factors were determined. Of the isolates, 85.9% were confirmed as E. coli strains. Among the 213 E. coli isolates tested, 94.8% (202/213) showed resistance for at least one antimicrobial, mainly ampicillin (83.0%; 177/213), cephalothin (76.0%; 162/213), and tetracyclines (69.0%; 147/213). In all the other antibiotics tested, the resistance percentage was below 36%. A multidrug-resistant phenotype was found in 72.7% of the tested strains. The presence of the tet gene (tetA or tetB) was detected in 43.1% of the isolates, the strA gene in 17.3%, and aadA1 in 51.6%. The blaTEM and blaSHV genes were found in 10.3 and 0.4% of the isolates, respectively. stx1 was detected in 4.2% of isolates, stx2 in 7.0, and hlyA in 2.8%. The virulence genes, eae and bfp, were not detected in any strain. These results indicate that Tamaulipas food products of bovine origin can be a source of multiresistant E. coli strains for the environment and exposure for consumers.